The Influence of Non-Permanent Employee’s Performance on Work Environment at BPJS LIAISON Office Rungkut Surabaya - Yogi Yunanto; Fendy Suhariadi; Praptini Yulianti (Universitas Warmadewa, 2019)
Human resources have a large role in an organization. The success in achieving organizational goals comes from the treatment of its own employees, therefore its employees will form the organizational structure and utilize technology. The aim of the study to know the employees’ role and respond to variations and measurements of the environment in the organization. Method of data analysis in this satudy is multiple linear regression. The steps of the analysis are as follows: analysis of data in the form of numbers in order to determine the effect of one variable with another. As for the methods used by statistical calculations according to (Pramono & Ferdinand, 2012. Therefore, the BPJS Health Liaison Office in Rungkut Surabaya expects that employees, both permanent and non-permanent, will have good performance. Employee performance will be better if the employee has high ability and a supportive work environment in completing his duties. Based on data analysis and discussion of research results. The results show that there is a partial influence of the work environment on the performance of temporary employees of BPJS Health Liaison Office Rungkut Surabaya.